2017
DOI: 10.1016/j.rbre.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plantar foot sensitivity manipulation on postural control of young adult and elderly

Abstract: Elderly subjects seem to rely more on foot sensitivity for control of body sway than young adults. In the elderly, a clinical intervention to improve foot sensitivity may help in upright posture maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…[4][5][6]19,26,27 Older people presented worse foot sensitivity compared to young adults. [4][5][6]27 At issue is the fact that the impact of less accurate sensory information on body position for postural control in older people is task-dependent. Thus, less accurate proprioceptive information is more detrimental to postural stability, especially in more challenging tasks.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]19,26,27 Older people presented worse foot sensitivity compared to young adults. [4][5][6]27 At issue is the fact that the impact of less accurate sensory information on body position for postural control in older people is task-dependent. Thus, less accurate proprioceptive information is more detrimental to postural stability, especially in more challenging tasks.…”
Section: Discussionmentioning
confidence: 99%
“… reported that plantar tactile sensitivity of first metatarsophalangeal joint affects balance and functional performance in older people. There are also studies indicating plantar tactile sensitivity reduction is associated with postural sway . However, some studies suggest that plantar sensitivity is moderately important for sustaining the upright balance and the effect of decreased plantar sensation on balance is compensated by other sensory systems .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, [11] suggest that walking barefoot is less restricting for motion control, which increases the sensitivity of the sensory mechanisms and activates the foot and lower leg muscles. Both sensory feedback sensitivity [12] and increased foot strength [13] showed to improve balance in older adults, and are therefore significant predictors in the prevention of falls. Thus, barefoot walking might result in beneficial effects on sensorimotor control.…”
Section: Introductionmentioning
confidence: 99%